2019
DOI: 10.1016/j.biopsych.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Noncoding RNA Postmortem With Suicide by Violent Means and In Vivo With Aggressive Phenotypes

Abstract: Objective: Previous findings suggest that differences in brain expression of a humanspecific long intergenic non-coding RNA (LINC01268; GRCh37/hg19: LOC285758) may be linked to aggressive behavior and suicide. The authors sought to replicate and extend these findings in a new sample, and translate the results to the behavioral level in living healthy subjects. Method:The authors examined RNA sequencing data in human brain to confirm the prior postmortem association of the lincRNA specifically with suicide by v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Transcriptome sequencing and qRT-PCR con rmed that lncRNA SMIM25 was high expression in cerebral cavernous malformations on the before study [42]. LINC01268 could in uence the emotional regulation, and was involved in gene regulation of potential immune response [43]. The alias of GS1-358P8.4 is PDK3, the study reported that high expressions of PDK3 were poor prognostic factors of acute myeloid leukemia [44].…”
Section: Discussionmentioning
confidence: 87%
“…Transcriptome sequencing and qRT-PCR con rmed that lncRNA SMIM25 was high expression in cerebral cavernous malformations on the before study [42]. LINC01268 could in uence the emotional regulation, and was involved in gene regulation of potential immune response [43]. The alias of GS1-358P8.4 is PDK3, the study reported that high expressions of PDK3 were poor prognostic factors of acute myeloid leukemia [44].…”
Section: Discussionmentioning
confidence: 87%
“…Since chronically isolated mice have altered behaviors toward other individuals, such as increased aggression but also blunted response to social novelty (Zelikowsky et al, 2018), it is possible that lncRNAs are important modulators of behavioral responses due to chronic social isolation in mammals. Consistently, aggressive behaviors have also been associated with changes in lncRNAs expression (Punzi et al, 2019;Labonté et al, 2020). The monoamine oxidase A (MAOA) associated ncRNA (MAALIN) is a lncRNA located in the 3 intergenic region separating the tail-to-tail oriented MAO genes A and B.…”
Section: Lncrnasmentioning
confidence: 94%
“…LOC28758 is located in the MARCKS gene, which was also found to be significantly highly expressed in violent suicides than non-suicides and non-violent suicides. In a recent study, the authors also examined lncRNA expression changes in dlPFC by RNA-seq (28). LINC01268 expression was significantly higher in suicide subjects compared to non-suicide subjects.…”
Section: Long Non-coding Rnas In Psychiatric Disordersmentioning
confidence: 99%
“…Brain expressed ncRNAs can also influence the development of psychiatric disorders such as schizophrenia (SCZ), major depressive disorder (MDD), and bipolar disorder (BD) as well as neurodegenerative disorders ( 11 , 19 , 23 , 26 , 27 ). More recently, their role in suicidal behavior has been postulated ( 28 30 ). The effects of ncRNA expression changes are not restricted to the type of psychiatric disorders but, to a large extent, to different brain regions.…”
Section: Introductionmentioning
confidence: 99%